Performance Analysis of an F-Shaped Antenna for Wireless Applications - A. Gokula Chandar; S. Kannadhasan; R. Nagarajan; Parameswari Subbian; Mahtab Mashuq Tonmoy (International Journal of Antennas and Propagation)
The wide-band circularly polarised (CP) monopole antenna structure described in this article combines a defective ground plane with an f-shaped radiating monopole that is intended for impedance bandwidth and high axial ratio bandwidth (IBW). The faulty ground structure is etched as twin rectangular slots, an F-shaped slot, and a square slot with a corner cut off. The proposed antenna is 25 × 25 × 1.6 mm3 in total. The prototype of the optimised antenna’s far-field characteristics has been constructed, modelled, and experimentally confirmed. The simulated and measured return loss values are 3.19 to 7.4 GHz, with −32.48 dB and −38.42 dB, respectively. Axial ratio values are 4.37 to 7.22 GHz and 4.52 to 7.15 GHz, with an efficiency of 49.18% and 45.07%, respectively, for the simulated and observed bands. Gain levels in the whole CP band range from 2.8 to 3.3 dB. A continuous radiation efficiency of more than 90% is realised in the CP band. The suggested CP antenna has constant radiation qualities and is suitable for WLAN and WiMAX applications.